2007
DOI: 10.1080/10715760701291647
|View full text |Cite
|
Sign up to set email alerts
|

Indices of oxidative stress in pregnancy with fetal growth restriction

Abstract: Intrauterine fetal growth restriction (IUGR), the main cause of premature delivery and fetal mortality, has been suggested to involve oxidative stress. We found elevated values of indices of oxidative stress in the blood serum of pregnant women with IUGR: increased levels of malondialdehyde and 4-hydroxyalkenals, decreased activity of alpha-1-antitrypsin and decreased total antioxidant capacity of the serum, with respect to healthy pregnancy. Twenty day treatment with 3 g of l-arginine and 75 mg of acetylsalic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…In the absence of fetal genetic abnormalities, IUGR is often ascribed to placental insufficiency (Wareing et al, 2006), because it is often associated with extensive atherosclerotic and thrombotic lesions in the placental arteries and with placental infarction (Stuart et al, 1981). Placental oxidative stress, defective trophoblast invasion of arterioles, and RUPP similar to that seen in PE may be the underlying pathogenic mechanisms of both idiopathic IUGR and PE/IUGR pregnancies (Figueroa and Maulik, 2006;Karowicz-Bilinska et al, 2007).…”
Section: B Prostacyclin Metabolism and Intrauterine Growth Restrictionmentioning
confidence: 99%
“…In the absence of fetal genetic abnormalities, IUGR is often ascribed to placental insufficiency (Wareing et al, 2006), because it is often associated with extensive atherosclerotic and thrombotic lesions in the placental arteries and with placental infarction (Stuart et al, 1981). Placental oxidative stress, defective trophoblast invasion of arterioles, and RUPP similar to that seen in PE may be the underlying pathogenic mechanisms of both idiopathic IUGR and PE/IUGR pregnancies (Figueroa and Maulik, 2006;Karowicz-Bilinska et al, 2007).…”
Section: B Prostacyclin Metabolism and Intrauterine Growth Restrictionmentioning
confidence: 99%
“…Dysfunctions of several molecules, such as nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, alpha-1-antitrypsin (SERPINA1), insulin-like growth factor (IGF) and vascular endothelial growth factor (VEGF), might correlate with abnormal trophoblast invasion and vascular development, and oxidative stress in the placenta of FGR subjects [16,17,18,19,20,21,22]. The expression levels of apoptosis associated factors, such as ATP-dependent RNA helicase (DDX42), Bcl-2, p53, low-density lipoprotein (LDL), apo B and matrix metalloproteinases, changed during FGR development [6,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of oxidative stress have been described in serum of pregnant women with IUGR [6]. In fact, the blood plasma levels of TBARS from Pregnant women with IUGR were significantly increased as compared with control pregnant women (gestational control, 2.38±0.17 nmoles MDA/ml plasma vs IUGR, 5.32 ± 0.49 nmoles MDA/ ml plasma, n=10, p<0.001).…”
Section: Resultsmentioning
confidence: 79%
“…It has also been reported that oxidative DNA damage is increased in IUGR placenta [5]. Furthermore, other authors have shown increased levels of lipid peroxidation (TBARS, conjugated dienes and lipid peroxides) and decreased antioxidant capacity in serum of pregnant women with IUGR [6].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation